PARALLEL KORPUS MASHINA TARJIMASINING O‘RGANISH OBYEKTI SIFATIDA («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article is devoted to the types of parallel corpora, their importance, and the problems of their creation, as well as the development of machine translation.
Keywords: corpus linguistics, parallel corpus texts (PKM), machine translation, English and Norwegian Parallel Corpus, CzEng parallel corpus, Scielo parallel corpus, FAPESP parallel corpus.